Salivary characteristics in patients with familial Alzheimer’s disease due to e280a mutation - Palacio-Gutiérrez, Santiago; Marín-Sierra, Jhoann Mauricio; Echeverry, Anderson Andrés; Duque-Ramírez, Kevin Daniel; Jaramillo-Delgado, Gonzalo; Luna-Maldonado, Ernesto (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: Alzheimer’s disease is a neurodegenerative disorder characterized by the loss of cognitive functions. The prevalence of this disease worldwide is high, and therefore it is important to have a better understanding of the oral health needs and conditions of individuals with this disorder. The present study was carried out in a population with E280A mutation for Alzheimer’s disease. The goal was to describe the salivary characteristics of persons with early familial Alzheimer’s disease, in order to detect changes in the oral microbiome that can guide the dental management of these patients. Methods: transversal study in 37 participants living in the Metropolitan Area of the city of Medellín, aged 53 ± 6 years in average, in different stages of the disease: mild: 8, moderate: 7, and severe: 22, and evaluated by neuropsychological tests. Salivary samples were collected, evaluating saliva secretion rate and saliva buffer capacity, and conducting microbial analysis of the species most commonly found in the mouth. Results: 45.9% of participants showed a decreased rate of stimulated salivary secretion; salivary buffer capacity was decreased in 83.87% of participants, with average pH values of 3.449 ± 0.89 after the Ericsson test. Buffer capacity was altered in participants with decreased secretion rate and in those with no alteration in salivary secretion rate. High levels of microbial growth were observed, mainly for Streptococcus mutans and Candida albicans. Conclusions: This study suggests that other factors besides the pharmacological ones, like age and disease severity, may affect the salivary rate flow in patients with early familial Alzheimer’s disease.